ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEIKUTSERTAAN KELAS IBU HAMIL JANUARI – JULI TAHUN 2017 (Studi di Kecamatan Muara Tembesi Kabupaten Batang Hari Provinsi Jambi) - Emiyanti, Emiyanti; Rahfiludin, M. Zen; Winarni, Sri (Jurnal Kesehatan Masyarakat (Undip), 2017)
Pregnant Women Class routinely implemented in Batang Hari Regency since last 5 years, the number of pregnant women who have attended pregnant women's classes in Batang Hari Regency in 2015 was 83%, But in Muara Tembesi District, the percentage of pregnant women who visited the class of pregnant women was lower than in Batang Hari Regency (45.5%). The aim of this research was to analyze factors related to participation of pregnant women class in Muara Tembesi District, Batang Hari Regency, Jambi Province. The type of research is explanatory research with cross sectional study design. Research population were all pregnant women in Muara Tembesi District which were 265 pregnant women. Research samples were 71 respondents with simple random sampling. Data was collected using questionnaire and analyzed by univariate and bivariate by using chi square test. The results showed the majority of pregnant women who attended the class of pregnant women (62.0%), Well-informed mother (67,6%) and husband support (62.0%). The results showed correlations of knowledge of pregnant women class (p value= 0,013), attitude towards pregnant women class (p value= 0,040), and husband support (p value= 0,033) with participation of pregnant women class. Age, education, occupation and gravide variables were not correlate with participation of pregnant women. The suggestion to midwife as facilitator of pregnant mother class can promote class activities of pregnant mother and more to increase knowledge of pregnant mother about the benefits of iron tablets and laboratory test when giving antenatal care service through counseling, simulation and interpersonal communication.